Development and Validation of an Instrument to Measure Students' Motivation and Self-Regulation in Science Learning - Velayutham, Sunitadevi; Aldridge, Jill; Fraser, Barry (Routledge, 2011)
Students’ motivational beliefs and self‐regulatory practices have been identified as instrumental in influencing the engagement of students in the learning process. An important aim of science education is to empower students by nurturing the belief that they can succeed in science learning and to cultivate the adaptive learning strategies required to help to bring about that success. This article reports the development and validation of an instrument to measure salient factors related to the motivation and self‐regulation of students in lower secondary science classrooms. The development of the instrument involved identifying key determinants of students’ motivation and self‐regulation in science learning based on theoretical and research underpinnings. Once the instrument was developed, a pilot study involving 52 students from two Grade 8 science classes was undertaken. Quantitative data were collected from 1,360 students in 78 classes across Grades 8, 9, and 10, in addition to in‐depth qualitative information gathered from 10 experienced science teachers and 12 Grade 8 students. Analyses of the data suggest that the survey has strong construct validity when used with lower secondary students. This survey could be practically valuable as a tool for gathering information that may guide classroom teachers in refocusing their teaching practices and help to evaluate the effectiveness of intervention programmes.